Células CD3+, CD4+, CD8+, CD3-CD16+CD56+ e CD19+ em sangue periférico de pacientes com hanseníase e indivíduos saudáveis - Pinheiro, Catiussia Dantas (2013)
Leprosy is an infectious and granulomatous disease caused by Mycobacterium leprae. The aim of this study was to quantify and compare levels of leucocytes and lymphocyte subpopulations (CD3+, CD3+CD4+, CD3+CD8+, CD19+, CD3-CD16+CD56+) in peripheral blood ofpatients with leprosy and healthy controls. Patients were followed at Centro de Dermatologia D. Libânia, Fortaleza-CE, Brasil. Flow cytometry was used to determine numbers of lymphocytes. Statistical analisys was done with GraphPad Prism 5.0 software for windows. P values under 0.05 were considered siginificant.This was an observational case-control study. Fifteen leprosy patients without treatment were evaluated and 29 healthy individuals were included in control group. NK cells (CD3-CD16+CD56+) mean in leprosy patients was 147(±113,4) and in controls was 378,1 (±231,7). Comparisson stablished a p value of 0.0008. B lymphocytes (CD19+) mean in leprosy patients was 233,3 (±85,89) and in controls was 115,3 (±53,01), with p < 0,0001 . No differences were observed in CD3+ T lymphocytes, CD4+ T lymphocytes and CD8+T lymphocytes. This study suggests that NK cells may play a role in innate response to M. leprae.